Assay of Yohimbine Chloride in Bulk Samplesand Pharmaceutical Formulations by Extractive Spectrophotometry - Begum, Jameelunnisa; Somasekhara Rao, Kaza; Rambabu, C. (Asian Journal of Chemistry, 2010)
Three simple and sensitive spectrophotometric methods (A–C) for the assay of yohimbine chloride in pure and dosage forms based on the formation of chloroform soluble ionassociates under specified experimental conditions are described. Three acidic dyes, namely, wool fast blue BL (WFB BL, Method A), tropaeolin-000 (Tp000, Method B) and naphthol blue 12BR (NB 12BR, Method C) are utilized. The extracts of the ion-associates exhibit absorption maxima at 580, 480 and 595 nm for methods A, B and C, respectively. Beer's law and the precision and accuracy of the methods are checked by the UV reference method. The results are reproducible with an accuracy of ± 1.0%. The methods are found to be suitable for the determination of yohimbine chloride in the presence of the other ingredients that are usually present in dosage forms.